CIRI HUMANISTIK PASTORAL ROMO JANSSEN - Maeja, Jhon Daeng; Meldison, Fransiskus; Wiwin, Wiwin (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Church and science have been at odds. The Church accuses science and vice versa. This opposition began to disappear when some figures reconciled this opposition. Science and religion are collaborated to achieve one particular goal. One of the figures who elaborated on the two is Father Janssen. The purpose of this study is to examine Father Janssen's pastoral relationship with humanistic psychology. Research using the library research method. The results showed that Father Jannsen applied humanistic psychology in his pastoral practice, especially in the field of education dan foundations established. The conclusion of the study is that the field of psychology that Father Janssen specializes in is practiced in his pastoral.